Nature and Environment: The Psychology of Its Benefits and Its Protection - Marc Glenn Berman (Frontiers Research Topics, 2017)
Our Research Topic section entitled: "Nature and the environment: The psychology of its benefits and its protection" will have two main lines. The first line of articles will center upon cutting-edge research showing how interacting with nature, can affect health, well-being, and overall improve cognition and affect. Articles in this line will stress in what ways nature can improve psychological functioning and health and also discuss the theories and evidence as to why nature can improve psychological functioning. For this line, we welcome submission of articles that discuss the psychological, health and well-being benefits from interacting with nature as well as submissions that focus on theoretical considerations and underlying mechanisms that lead to the restorative effects of interacting with nature. Given that nature can have a positive impact on psychological functioning and overall health, it is also important to understand the variables that facilitate people's recognition of environmental issues that can help foster a more positive attitude towards the preservation of nature. This brings us to the second line of articles which will center upon the psychological mechanisms that make individuals more or less likely to accept the seriousness of environmental challenges such as climate change. Given the new cutting-edge research in this field we may be able to make individuals more proactive in the protection of the environment and more accepting of policy measures required to mitigate climate change. We see this research topic as a way for psychological scientists to contribute substantially to an important area of public debate and policy. For this line we welcome articles that will focus on ways in which people respond to various framings of policy relevant information and how morality may play into the individuals policy views that center on climate change and environmental protection.